GluA1 phosphorylation at serine 831 in the lateral amygdala is required for fear renewal - Lee, Sukwon; Song, Beomjong; Kim, Jeongyeon; Park, Kyungjoon; Hong, Ingie; An, Bobae; Song, Sangho; Lee, Jiwon; Park, Sungmo; Kim, Jihye; Park, Dongeun; Lee, C. Justin; et al. (NATURE PUBLISHING GROUP, 2013)
Fear renewal, a widely pursued model of post-traumatic stress disorder and phobias, refers to the context-specific relapse of conditioned fear after extinction. However, its molecular mechanisms are largely unknown. We found that renewal-inducing stimuli, generally believed to be insufficient to induce synaptic plasticity, enhanced excitatory synaptic strength, activity of synaptic GluA2-lacking AMPA receptors and Ser831 phosphorylation of synaptic surface GluA1 in the lateral nucleus of the amygdala (LAn) of fear-extinguished rats. Consistently, the induction threshold for LAn synaptic potentiation was considerably lowered after extinction, and renewal occluded this low-threshold potentiation. The low-threshold potentiation (a potential cellular substrate for renewal), but not long-term potentiation, was attenuated by dialysis into LAn neurons of a GluA1-derived peptide that competes with Ser831-phosphorylated GluA1. Microinjections of the same peptide into the LAn attenuated fear renewal, but not fear learning. Our findings suggest that GluA1 phosphorylation constitutes a promising target for clinical treatment of aberrant fear-related disorders.
Keywords: LONG-TERM POTENTIATION; DEPENDENT NEURONAL-ACTIVITY; AMPA RECEPTOR ENDOCYTOSIS; SYNAPTIC PLASTICITY; CONDITIONED FEAR; GLUTAMATE RECEPTORS; CHANNEL CONDUCTANCE; KINASE-II; EXTINCTION; MEMORY